Correction to: Economic burden of multiple sclerosis in a population with low physical disability - José M. García-Domínguez; Jorge Maurino; María L. Martínez-Ginés; Olga Carmona; Ana B. Caminero; Nicolás Medrano; Elena Ruíz-Beato; for the W-IMPACT Clinical Investigators (BMC, 2019)
It has been highlighted that the original article [1] contained a mistake in the 'Results' section, specifically in the percentages of female subjects and those with diagnosis of RRMS. Please note that this mistake has only been present in the 'Results' section, the Abstract and Table 1 remain unchanged. This article shows the incorrect and correct version of the percentages.